Flow diversion with Pipeline Embolic Device as treatment of subarachnoid hemorrhage secondary to blister aneurysms: dual-center experience and review of the literature. (13th April 2016) - Linfante, Italo; Mayich, Michael; Sonig, Ashish; Fujimoto, Jena; Siddiqui, Adnan; Dabus, Guilherme
Abstract : Background: Aneurysmal subarachnoid hemorrhage (aSAH) secondary to blister-type aneurysms (BAs) is associated with high morbidity and mortality. Microsurgical clipping or wrapping and/or use of traditional endovascular techniques to repair the lesion result in frequent regrowth and rebleeds and ultimately high fatality rates. Because of the purely endoluminal nature of arterial reconstruction, flow diversion may represent an ideal option to repair ruptured BAs. Methods: We performed a retrospective analysis of our database including all consecutive patients with aSAH secondary to BAs treated with the Pipeline Embolic Device (PED) between November 2013 and November 2015 in two institutions. We collected basic patient demographics, aneurysm size, location, number and sizes of PEDs used, use of coiling, 30-day modified Rankin Scale (mRS) score, and follow-up imaging data. Results: Ten cases of aSAH were found as a result of a ruptured BA. Patients had a mean age of 47.2 years (range 27–68). Mean Hunt and Hess score was 1.6 (range 1–4). Lesions were predominantly left-sided, mostly along the dorsal aspect of the internal carotid artery, either paraclinoid or paraophthalmic (8/10). In two patients the BA was located in the left middle cerebral artery. All lesions were very small (mean 1.4×1.5 mm; range 0.75–2.1 mm). Placement of a single PED resulted in immediate occlusion or near-occlusion of the BA in 9 out of 10 patients. Nine patients did very well; eight had a 90-day mRS score of 0 and one had a 90-day mRS score of 1. Follow-up digital subtraction angiography was performed in all patients (mean 15 months; range 7–24). In the surviving nine patients there was complete occlusion of the BA on long-term follow-up angiography. Conclusions: Repair of ruptured BA with PED may be a safe and durable option.